2016
DOI: 10.18632/oncotarget.12706
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26b suppresses cell proliferation and invasion by targeting cyclooxygenase 2 in human glioblastoma

Abstract: MiRNAs are emerging as important epigenetic modulators of multiple target genes, leading to abnormal cellular signaling involving cellular proliferation in cancers. Aberrant miRNA expression has been observed in human glioblastoma (GBM). The present study was to evaluate the expression and molecular mechanisms of COX-2 and miR-26b in human GBM tissues and GBM cell lines T98G, U87 and U251. In the present study, we found that expression of miR-26b was markedly downregulated in GBM cell lines and human GBM tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been reported as a pivotal factor in multiple physiological functions and pathological processes, including inflammation and tumorigenesis ( 10 ). Previous studies have shown that Cox-2 has a negative correlation with the expression of several miRNAs, such as miR-26b ( 11 ), miR-203 ( 12 ), and miR-335 ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported as a pivotal factor in multiple physiological functions and pathological processes, including inflammation and tumorigenesis ( 10 ). Previous studies have shown that Cox-2 has a negative correlation with the expression of several miRNAs, such as miR-26b ( 11 ), miR-203 ( 12 ), and miR-335 ( 13 ).…”
Section: Introductionmentioning
confidence: 99%